Mortal Kombat or how to save the world - Sitarski, Piotr (Replay. The Polish Journal of Game Studies, 2014)
The paper analyses interrelations between different constituents of the Mortal Kombat entertainment system. The author points out those specific features of movie adaptations that are necessitated by the characteristic of the original games (lack of meaningful plot being one of them). In the last part of the paper the author interprets the Mortal Kombat entertainment system as a training exercise for contemporary consumerist lifestyle.